Палеоліт Центральної України - Залізняк, Л.Л. (Археологія, 2014)
Пропонується періодизація культурних явищ палеоліту Центральної України (Кіровоградщини, Черкащини та прилеглих до них регіонів). Девять лет исследований ранее неизвестного скопления палеолитических стоянок в бассейне р. Большая Высь на Кировоградщине позволили разработать периодизацию культурных явлений палеолита центральных областей Украины и, прежде всего, Черкасской и Кировоградской. Особенно пестрой культурноисторическая картина была во время средневюрмского потепления (55—27 тыс. лет назад), создавшего условия для колонизации людьми современного типа Европейского континента. В это время в центральных областях Украины формировались бурые витачевские грунты. В них залегали культурные слои стоянок зубчатого мустье, мустье одностороннего (Андреев ка 4, верхний и нижний слои), памятников типа Коробчино, селетского (Высь, Мира) и ориньякского (Ворона ІІІ) технокомплексов. Судя по данным геологии и типологическим параллелям, памятники датируются концом среднего – началом верхнего палеолита, когда в регионе обитали как автохтонынеандертальцы, так и кроманьонцы.
Исследована группа граветских стоянок Трояново 4А и 4В, Озерово, ближайшие аналогии которым имеются в материалах граветских стоянок Поднестровья. Полученные материалы свидетельствуют о продвижении носителей граветских традиций молодовской культуры из бассейна Днестра далеко на восток почти до Среднего Днепра. Судя по залеганию этих материалов в бугских лесах, граветские стоянки Кировоградщины функционировали во время максимального похолодания — в средний период верхнего палеолита (27—19 тыс. лет назад).
На позднем этапе верхнего палеолита (19—12 тыс. лет назад) на территории центральных областей Украины развивалась происходящая от гравета эпиграветская культурная традиция (Владимировка, слои 1—6, Межиричи, Анетовка ii). В финальном палеолите на основании эпиграветских традиций сформировались осокоровская и шанкобинская культуры юга Украины.
В целом культурноисторические явления палеолита Центральной Украины были локальными проявлениями общеевропейских палеолитических единств. Большинство из них имеют прямые параллели на западе. Другими словами, палеолит Кировоградщины и Черкащины, как и всей Украины, в культурноисторическом отношении был органической, неотъемлемой частью палеолита Европи. ten years of research at the not known before Palaeolithic sites gathering in the velyka vys river basin in kirovohrad region allowed the author to develop the division into periods of cultural phenomena in the Palaeolithic in central Ukrainian Ob lasts, first of all in Cherkasy and kirovohrad Oblasts. Cultural and historical picture was especially variegated in the Middle Würm interglacial period (55—27 millenia BP) which created the conditions for colonization by the modern type people of the european continent. Brown vytachiv soils were forming in the central Ukrainian Oblasts at this period. they contained cultural layers of denticulated and of onesided Mousterian (andriyivka 4, upper and lower layers), sites of korobchyne type, of szelet (vys, Mira), and of aurignaс (vorona iii) technological assemblages. Judging from the geological data and from typological parallels, the sites are dated by the period from the end of the Middle Palaeolithic to the beginning of the Upper Palaeolithic when both the autochthonous neanderthals and the CroMagnons inhabited the region.
studied is a group of Gravettian sites, troyanove 4a and 4B, and Ozerove, the closest analogies to which are there in the Gravettian materials from the sites in the Dnister river region. the materials obtained testify that the Gravettian traditions bearers of Molodove culture moved far eastward from the Dnister river basin almost to the Dnipro river middle region. according to the laying of these materials in the forests near the Buh river, the Gravettian sites of kirovohrad region func tioned during the highest glaciations, i.e. in the middle period of the Upper Palaeolithic (27—19 millennia BP).
at the late stage of the Upper Palaeolithic (19—12 millennia BP), epiGravettian cultural tradition (volodymyrivka, layers 1—6, Mezhyrichi, anetivka ii) originating from Gravettian developed on the territory of the central Ukrainian Ob lasts. Osokorivka and shankoba cultures of the south of Ukraine created on the base of epiGravettian traditions in the Final Palaeolithic.
as a whole, cultural and historic phenomena of Palaeolithic period in Central Ukraine are local displays of general european Palaeolithic unities. Most of them find direct parallels in the West. in other words, Palaeolithic in kirovohrad and Cherkasy regions, as well as in the whole Ukraine, is culturally and historically an organic and integral part of the Pal aeolithic in europe.